Сandidate SNP-markers of rheumatoid arthritis that can significantly alter the affinity of the TATA-binding protein for human gene promoters - I. V. Chadaeva; D. A. Rasskazov; E. B. Sharypova; I. A. Drachkova; E. A. Oshchepkova; L. K. Savinkova; P. M. Ponomarenko; M. P. Ponomarenko; N. A. Kolchanov; V. A. Kozlov (Вавиловский журнал генетики и селекции)
Rheumatoid polyarthritis (RA) is an autoimmune disease with autoantibodies, including antibodies to citrullant antigens and proinflammatory cytokines, such as TNF-α and IL-6, which are involved in the induction of chronic synovitis, bone erosion, followed by deformity. Immunopathogenesis is based on the mechanisms of the breakdown of immune tolerance to its own antigens, which is characterized by an increase in the activity of T-effector cells, causing RA symptomatology. At the same time, against the background of such increased activity of effector lymphocytes, a decrease in the activity of a number of regulatory cells, including regulatory T-cells (Treg) and myeloid suppressor cells, is recorded. There is reason to say that it is the change in the activity of suppressor cells that is the leading element in RA pathogenesis. That is why only periods of weakening (remission) of RA are spoken of. According to the more powerful female immune system compared to the male one, the risk of developing RA in women is thrice as high, this risk decreases during breastfeeding and grows during pregnancy as well as after menopause in proportion to the level of sex hormones. It is believed that 50 % of the risk of developing RA depends on the conditions and lifestyle, while the remaining 50 % is dependent on genetic predisposition. That is why, RA fits the main idea of postgenomic predictive-preventive personalized medicine that is to give a chance to those who would like to reduce his/her risk of diseases by bringing his/her conditions and lifestyle in line with the data on his/her genome sequenced. This is very important, since doctors consider RA as one of the most frequent causes of disability. Using the Web service SNP_TATA_Z-tester (http://beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan_fox/start.pl), 227 variants of single nucleotide polymorphism (SNP) of the human gene promoters were studied. As a result, 43 candidate SNP markers for RA that can alter the affinity of the TATA-binding protein (TBP) for the promoters of these genes were predicted.